Nietzsche, power and politics. The 16th international conference - de Santiago Guervós, Luis Enrique (Estudios Nietzsche, 2007)
Noticia sobre el congreso de la Friedrich Nietzsche Society of Great Britain and Ireland: Nietzsche, power and politics. The 16th international conference